Transcriptional Activation by NFκB Increases Perlecan/HSPG2 Expression in the Desmoplastic Prostate Tumor Microenvironment. Issue 7 (July 2014) - Warren, Curtis R.; Grindel, Brian J.; Francis, Lewis; Carson, Daniel D.; Farach‐Carson, Mary C.
ABSTRACT Perlecan/HSPG2, a heparan sulfate proteoglycan typically found at tissue borders including those separating epithelia and connective tissue, increases near sites of invasion of primary prostatic tumors as previously shown for other proteins involved in desmoplastic tissue reaction. Studies of prostate cancer cells and stromal cells from both prostate and bone, the major site for prostate cancer metastasis, showed that cancer cells and a subset of stromal cells increased production of perlecan in response to cytokines present in the tumor microenvironment. In silico analysis of the HSPG2 promoter revealed two conserved NFκB binding sites, in addition to the previously reported SMAD3 binding sites. By systematically transfecting cells with a variety of reporter constructs including sequences up to 2.6 kb from the start site of transcription, we identified an active cis element in the distal region of the HSPG2 promoter, and showed that it functions in regulating transcription of HSPG2. Treatment with TNF‐α and/or TGFβ1 identified TNF‐α as a major cytokine regulator of perlecan production. TNF‐α treatment also triggered p65 nuclear translocation and binding to the HSPG2 regulatory region in stromal cells and cancer cells. In addition to stromal induction of perlecan production in the prostate, we identified a matrix‐secreting bone marrow stromal cell type that may represent the source for increases in perlecan in the metastatic bone marrow environment. These studies implicate perlecan in cytokine‐mediated, innate tissue responses to cancer cell invasion, a process we suggest reflects a modified wound healing tissue response co‐opted by prostate cancer cells. J. Cell. Biochem. 115: 1322–1333, 2014. © 2014 Wiley Periodicals, Inc.